Seleksi Isolat Bakteri Endofit Selulolitik Strain Lokal dari Akar Mangrove Ceriops tagal (Perr) C. B. Rob - Itnawita Itnawita; Silvera Devy; Mukhlis Mukhlis; Alfika Sari (LPPM Universitas Muhammadiyah Riau, 2022)
Cellulose agricultural waste is a source of environmental pollution and an alternative solution to overcome it is to degrade this waste with the help of cellulolytic enzymes. The Biochemistry Laboratory of FMIPA Riau University has a number of endophytic bacterial isolates from the roots of Mangrove Ceriops tagal (Perr) C. B. Rob in the Bengkalis area whose potential to produce cellulolytic enzymes is not yet known. Qualitative selection in carboxy methyl cellulose (CMC) solid media from 24 isolates of endophytic bacteria that were able to live because they produced cellulolytic enzymes, only 22 isolates. Quantitatively using the DNS (Dinitro Salicylic Acid) method, 3 of these 22 isolates had relatively higher activity than other isolates. The activity of isolate C-9 (LBKURCC332) was 572x10-4±0.0069U/mL, isolate C-23(LBKURCC346) was 423x10-4±0.0027U/mL and isolate C-30 (LBKURCC353) was 384x10-4± 0.0003 U/mL and statistically these 3 cellulolytic activities were significantly different